Internet Protocol Television (IPTV) the killer application for the next-generation Internet. - Yang Xiao.
Internet protocol television (IPTV) will be the killer application for the next-generation Internet and will provide exciting new revenue opportunities for service providers. However, to deploy IPTV services with a full quality of service (QoS) guarantee, many underlying technologies must be further studied. This article serves as a survey of IPTV services and the underlying technologies. Technical challenges also are identified.
Keywords: IPTV services; QoS; Next-generation internet